Implementation of the Independent Curriculum with Islamic Religious Education to Develop Soft Skills Student - Siti Rahmawati; Fauziyah Qurrota A’yun Tamami; Mahmudulhassan Mahmudulhassan; Sabrina Failasufa Tamami (Bulletin of Islamic Research, 2025)
This study explores the implementation of the Independent Curriculum at SMP Muhammadiyah 2 Makamhaji Kartasura known as "SMP Muhammadiyah Duta", a small school with fewer than 50 students. Despite its limited resources, the school endeavors to optimize the learning goals of the Independent Curriculum introduced by Indonesia’s Ministry of Education and Culture. Employing a qualitative case study approach, data were collected through interviews, observations, and document analysis involving the principal, two teachers, and six students across grades 7–9. The findings reveal that the Independent Curriculum is applied progressively, with a focus on aligning educational strategies with local potential and student needs. The curriculum emphasizes adaptable and flexible lesson planning, integrating Islamic values across subjects, and continuous assessments to ensure learning objectives are met. Key outcomes include a learning design that holistically develops student competencies in knowledge, skills, and attitudes. Project-based learning and problem-solving activities enhance critical and creative thinking skills. The research underscores the vital role of parental and community involvement in supporting the learning process. This study contributes valuable insights into the practical implementation of the Independent Curriculum in small schools and provides a reference for other institutions aiming to adopt this model. It highlights the potential of well-designed curricula to foster independent, creative learners equipped to address future challenges effectively.